Future management of the Arctic National Wildlife Refuge [microform] : hearings before the Subcommittee on Environmental Protection of the Committee on Environment and Public Works, United States Senate, One Hundredth Congress, first and second sessions, on S. 1804 . December 10, 1987, February 17, 1988. - United States. Congress. Senate. Committee on Environment and Public Works. Subcommittee on Environmental Protection. (Washington : U.S. G.P.O., 1988)
CIS Microfiche Accession Numbers: CIS 88 S321-53 Bibliography: p. 244-245. Microfiche. Mode of access: Internet.